2013
DOI: 10.1111/pme.12067
|View full text |Cite
|
Sign up to set email alerts
|

Effect on Pain Relief and Inflammatory Response Following Addition of Tenoxicam to Intravenous Patient-Controlled Morphine Analgesia: A Double-Blind, Randomized, Controlled Study in Patients Undergoing Spine Fusion Surgery

Abstract: The combination of T and M for IV-PCA was not more efficacious than IV-PCA with M alone in reducing postoperative pain after spine surgery but reduced PCA demand and suppressed local inflammation at the surgical site. Administration of T before wound closure may ameliorate IV-PCA M-induced skin itching.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…It was shown that itch is blocked by certain NSAIDs such as tenoxicam and diclofenac, in humans (Colbert et al 1999, Chang et al 2013). The effect of prostaglandins (PGs) on pruritus has also been researched in further studies including both human (Neisius et al 2002) and rodents (Andoh andKuraishi 1998, Takaoka et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that itch is blocked by certain NSAIDs such as tenoxicam and diclofenac, in humans (Colbert et al 1999, Chang et al 2013). The effect of prostaglandins (PGs) on pruritus has also been researched in further studies including both human (Neisius et al 2002) and rodents (Andoh andKuraishi 1998, Takaoka et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…), in postoperative pain management (decreasing morphine consumption) [13], in renal colic [14] and in dentistry in postendodontic pain [15], providing also a prophylactic anti-inflammatory effect. In combination with other analgesics (morphine), it has been investigated for its additive antinociceptive effect in postoperative intravenous patient-controlled analgesia [16]. …”
Section: Introductionmentioning
confidence: 99%
“…The 2 RCTs that tested paracetamol found that it was more effective than placebo and less effective than dexketoprofen in reducing pain scores . The RCTs that tested systemic lidocaine, ketorolac, and NSAIDs (tenoxicam) led to controversial results . Upton et al found that fentanyl administered while maintaining an Analgesia Nociception Index of > 50 with boluses of 50 μg (in patients < 50 years of age) or 25 μg (in patients > 50 years of age) was more effective than the “classic” administration …”
Section: Resultsmentioning
confidence: 99%
“…The 29 RTCs that tested therapies administered during the intraoperative period included systemic pharmacological therapies (19 studies) [48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66] and locoregional anesthetic drugs (10 studies) [67][68][69][70][71][72][73][74][75][76] (see Table 3).…”
Section: Intraoperative Therapiesmentioning
confidence: 99%